Strategy For The Shipping Decarbonisation Using Marine Diesel Oil - Kurniasih, Pritha; Runadi, Taruga; Amma, Muhammad (RSF Conference Series: Engineering and Technology, 2023)
Climate change has become a global problem. Transportation is one of the contributors to the problem of increasing carbon emissions. The world of shipping, as the most significant mode of transportation of goods worldwide, contributes to increasing carbon emissions. Greenhouse Gas Emission has led IMO to participate in implementing policies related to decarbonization in the maritime world, which began in 2020. This research aims to understand the use of Marine Diesel Oil as one of the strategies implemented to reduce the impact of carbon emissions. This study uses a qualitative research methodology using primary data based on observations on board and secondary data from reputable international journals. In addition, data analysis uses the SWOT matrix. The results of this study are to determine the strengths and weaknesses of using MDO, as well as opportunities and threats to using MDO in Emission Control Areas. The hope is that ECA can be expanded, especially in world shipping lanes, to minimize the impact of carbon emissions. In addition, more in-depth research on decarbonization in the maritime industry and the port area can be carried out.